2016
DOI: 10.1038/pr.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adjustment to postnatal growth trajectories in healthy preterm infants

Abstract: Background: International guidelines suggest that growth of preterm infants should match intrauterine rates. However, the trajectory for extrauterine growth may deviate from the birth percentile due to an irreversible, physiological loss of extracellular fluid during postnatal adaptation to extrauterine conditions. To which "new" physiological growth trajectory preterm infants should adjust to after completed postnatal adaptation is unknown. This study analyzes the postnatal growth trajectories of healthy pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 32 publications
13
108
3
Order By: Relevance
“…Although previously the stated goal for weight gain in the NICU was to achieve intrauterine growth velocities using calculations from standardized growth curves of preterm infants based on cross‐sectional data from infants born at various gestational ages, a recent review of evidence to support nutrition practice guidelines has questioned this approach . It has been suggested that attempting to achieve intrauterine growth rates based on maintaining a growth trajectory that follows the percentile found at birth (requiring a weight gain velocity of 15–17 g/kg/d depending on the growth curve) may not be appropriate because of obligatory weight loss due to fluid shifts during the first week of life . The authors suggested that a growth trajectory that has a goal of maintaining weight at discharge of ≥−0.8 z scores from the birth percentile may be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Although previously the stated goal for weight gain in the NICU was to achieve intrauterine growth velocities using calculations from standardized growth curves of preterm infants based on cross‐sectional data from infants born at various gestational ages, a recent review of evidence to support nutrition practice guidelines has questioned this approach . It has been suggested that attempting to achieve intrauterine growth rates based on maintaining a growth trajectory that follows the percentile found at birth (requiring a weight gain velocity of 15–17 g/kg/d depending on the growth curve) may not be appropriate because of obligatory weight loss due to fluid shifts during the first week of life . The authors suggested that a growth trajectory that has a goal of maintaining weight at discharge of ≥−0.8 z scores from the birth percentile may be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there are other opinions about the adjustment of postnatal growth trajectories because all neonates including very preterm infants lose extracellular fluid after birth and tend to follow a lower percentile than their birth percentile16). However, extrauterine growth restriction commonly occurs in neonatal units1718).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that using weight conflates changes in the extracellular fluid compartment and subsequent nutrition . In an ‘ideal’ preterm population, weight z score change of −0.8 within the first 2 weeks of life was demonstrated due to the contraction of the extracellular space and was maintained at least until day 21 – therefore, the post‐intervention z score change of −0.76 at 28 days may represent appropriate nutrition. However, by discharge, current recommendations are that birth z score should be regained …”
Section: Discussionmentioning
confidence: 99%